Energi Metabolis Semu dan Efisiensi Metabolik pada Serindit Sumatera (Loriculus galgulus L., 1758) - Sari, Andri Permata; Rachmatika, Rini (Perhimpunan Biologi Indonesia, 2014)
The animal obtains energy from foods. Apparent Metabolizable Energy (AME) is used to determine metabolizableenergy value of birdÃ¢â¬â¢s food. The objective of this research was to evaluate Apparent Metabolizable Energy (AME)value in Blue-crowned hanging parrot (Loriculus galgulus L., 1758), fed with corn mashes, oat mashes, dan pollardmashes. This research consisted of two experiments, which were 1 week of preliminary study and 8 weeks of datacollection. Studies were carried out with six Blue-crowned hanging parrots, two males and four females. The birdswere kept individually in metabolism cage (70 x 43 x 52 cm). The birds were treated with 3 different energy sources,corn-based diet (P1), oat-based diet (P2), and pollard-based diet (P3). The diets were then offered to the birds adlibitum in the form of mashes. Variables observed include dry matter consumption and Apparent MetabolizableEnergy (AME) value. From the calculation, AME of birds that fed with pollard mashes was higher compared to cornand oat mashes as well. In P1, AME value of birds was 43.64 cal/g with 93.90% of metabolic efficiency. While, inthe P2 and P3, AME value were 43.86 cal/g and 39.07 cal/g with number of metabolic efficiency 91.75% and94,58% respectively.Keywords: nutrition, pollard, oat, corn, AME, metabolic efficiency